Mediating Role of Self-Efficacy: Resiliency and Entrepreneurial Intention in Young Generation - Kurniawati, Regina Zaviera Anggi; Pangaribuan, Christian Haposan; Kembau, Agung Stefanus; Nilam, Edric Budiman (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Research Originality: While combining the TPB and Linan Model, this study provides novelty through its analysis of the underexplored role of financial resources and self-efficacy in shaping entrepreneurial intentions among the young generation. Research Objectives: The research investigates the resilience factors that shape entrepreneurial ambition, focusing on the direct effects of entrepreneurship education, creativity, and financial resources, as well as the indirect effect of entrepreneurial self-efficacy on the relationship between these factors and entrepreneurial intention. Research Methods: This study utilizes a questionnaire survey from 312 college students in Jakarta. Structural equation modeling (SEM) was used to analyze the data. Empirical Results: The findings show that financial resources, entrepreneurial education, and creativity influence self-efficacy. The associations between creativity and entrepreneurial intention, as well as between entrepreneurship education and entrepreneurial intention, are significant for the indirect paths that use self-efficacy as a mediator. Implications: We recommend that universities, governments, and other stakeholders prioritize initiatives that offer financial assistance and focus on educational programs and support systems that enhance confidence and belief in entrepreneurial capabilities. JEL Classification: L26, I23, O10